Out of many, one: integrating data in the paediatric cardiovascular environment. (29th September 2016) - Bradley, David J.; Wu, Danny T. Y.; Goldberg, Caren S.; Serwer, Gerald S.; Lowery, Ray E.; Donohue, Janet E.; Hirsch-Romano, Jennifer C.; Zheng, Kai; Pasquali, Sara K.
Abstract: Large volumes of data and multiple computing platforms are now universal components of paediatric cardiovascular medicine, but are in a constant state of evolution. Often, multiple sets of related data reside in disconnected "silos", resulting in clinical, administrative, and research activities that may be duplicative, inefficient, and at times inaccurate. Comprehensive and integrated data solutions are needed to facilitate these activities across congenital heart centres. We describe methodology, key considerations, successful use cases, and lessons learnt in developing an integrated data platform across our congenital heart centre.